The Influence of Using Audio Visual Media, Direct Demonstration and Learning Motivation on Learning Outcomes - Edy Widodo; Emy Dwi Nursulistyo; Fitri Anekawati; Andreas Subangkit (Institute of Advanced Knowledge and Science, 2024)
Learning outcomes are important for the success of learning in college. The purpose of this study was to test the effect of the use of audio visuals, direct roles, and learning motivation on learning outcomes. The results of the first hypothesis testing data analysis concluded that there was a difference in learning outcomes assisted by audiovisual media in combination with direct demonstrations with learning outcomes with only direct demonstrations (5.266> 2.00) and the significance value of the difference between the two learning outcomes was below 0.05. In addition, calculations using 2-way variance analysis obtained F count values ​​for direct demonstration media and audiovisual media obtained results greater than F table. The results of the second hypothesis testing data analysis concluded that there was a difference in learning outcomes between students who had high learning motivation and students who had low learning motivation, which was shown at 9.660 <2.857. By increasing learning outcomes, learning objectives can be achieved.